Evaluation of the Potential and Challenges of Implementing a Carbon Tax in Mitigating Climate Change in Indonesia - Zaenur Rahman; Mohamad Djasuli (Dinasti Publisher, 2024)
Carbon tax has been identified as an important instrument in efforts to mitigate climate change in Indonesia. This study aims to evaluate the potential and challenges of implementing a carbon tax in the Indonesian context. Through a policy analysis approach, this study investigates income potential, economic impact, and policy effectiveness in reducing carbon emissions. The study also identifies key challenges that may be faced, such as industry resistance, infrastructure limitations, and equitable distribution of tax proceeds. Quantitative and qualitative methods were used to analyze data related to the impact and implementation of carbon taxes in other countries while considering the social, economic, and political context of Indonesia. The study's findings provide important insights for policymakers to design and implement an effective carbon tax, taking into account Indonesia's unique conditions. It is expected that this research can be a significant contribution to developing a sustainable and competitive climate change mitigation strategy for Indonesia.